2002
DOI: 10.1364/ao.41.002043
|View full text |Cite
|
Sign up to set email alerts
|

Internal stress and optical properties of Nb_2O_5 thin films deposited by ion-beam sputtering

Abstract: The influence on the internal stress and optical properties of Nb2O5 thin films with ion-beam energy was investigated. Nb2O5 thin films were deposited on unheated glass substrates by means of ion-beam sputtering with different ion-beam voltage, Vb. The refractive index, extinction coefficient, and surface roughness were found to depend on the ion-beam energy. The stresses in thin films were measured by the phase-shifting interferometry technique. The film stress was also found to be related to Vb, and a high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Since NbO x or Nb 2 O 5 films are frequently used as optical thin films due to their high transmittance, high refractive index and chemical stability [28][29][30][31], we performed a brief characterisation of their optical properties. As shown in Fig.…”
Section: Structure and Properties Of The Deposited Nbo X Thin Filmsmentioning
confidence: 99%
“…Since NbO x or Nb 2 O 5 films are frequently used as optical thin films due to their high transmittance, high refractive index and chemical stability [28][29][30][31], we performed a brief characterisation of their optical properties. As shown in Fig.…”
Section: Structure and Properties Of The Deposited Nbo X Thin Filmsmentioning
confidence: 99%
“…Balog et al [7] performed further studies on V 2 O 5 at high temperature and pressure conditions (1500°C, 29 GPa) and confirmed that HPP1 and HPP2 are β-V 2 O 5 and B-V 2 O 5 , respectively. Moreover, the numerous excellent electrical, optical, and physical-chemical properties of M 2 O 5 have encouraged theoretical and experimental investigations of these compounds [8][9][10][11][12][13][14][15][16][17][18][19]. Given its large flux of ion implantation and outlet, large lithium-ion storage density, and stable properties in the polymer electrolyte, V 2 O 5 film might be applied in the electrode layer [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This film has been widely applied in various fields [11,12]. attention from researchers [13][14][15]; they have been applied in various optical thin films and photoelectronic devices [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many applications in photonics demand high refractive index materials with good optical quality and negligible scattering. Thus, various innovative applications have been developed and thin Nb 2 O 5 films have found applications in photonics for improving the optical performance of different devices such as optical filters [4], waveguide-based optical circuits [5], and transparent conductive electrodes [6]. A number of novel applications of Nb 2 O 5 films rely on the ability to deposit high quality films using relatively simple and inexpensive techniques such as sol-gel and spin or dip coating.…”
Section: Introductionmentioning
confidence: 99%